Characteristics of E-Mail Solicitations From Predatory Nursing Journals and Publishers. - Lewinski, Allison A.; Oermann, Marilyn H. (Journal of Continuing Education in Nursing, 2018)
Predatory publishers solicit manuscripts through e-mail invitations to potential authors, with the goal of enticing authors to submit a manuscript to the journal. This descriptive study examined the characteristics of 206 e-mail invitations from predatory journals and publishers sent to faculty and students in a school of nursing over a 10-week period. Characteristics of these e-mails included use of flattering language, due dates for submissions close to the date of the e-mail sent, requests for general topics, and awkward phrases. However, many e-mails did not have characteristics that clearly identified them as coming from a predatory journal or publisher. Education on predatory publishing is needed for all nurse authors, specifically how to identify and confirm whether a journal is predatory or legitimate.